6y+3(y-4)=3

Simple and best practice solution for 6y+3(y-4)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y+3(y-4)=3 equation:


Simplifying
6y + 3(y + -4) = 3

Reorder the terms:
6y + 3(-4 + y) = 3
6y + (-4 * 3 + y * 3) = 3
6y + (-12 + 3y) = 3

Reorder the terms:
-12 + 6y + 3y = 3

Combine like terms: 6y + 3y = 9y
-12 + 9y = 3

Solving
-12 + 9y = 3

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 9y = 3 + 12

Combine like terms: -12 + 12 = 0
0 + 9y = 3 + 12
9y = 3 + 12

Combine like terms: 3 + 12 = 15
9y = 15

Divide each side by '9'.
y = 1.666666667

Simplifying
y = 1.666666667

See similar equations:

| 14y=210 | | 10x+9y=-90 | | 6y+3z-x^2=x^2+z-70 | | 3x^2-4x+1000=0 | | -9(6x-3)=9-5(12x-6) | | 73=8-5b | | 2/3x*2/3x-6=0 | | -4=4m^2-10m+2 | | ft=m(x-y) | | 4(3x+2)-2=7 | | -56=-7(k+5) | | Y^2+4y+72=0 | | y-x=7x+2 | | 27*s^4=5 | | X+4x=2x-15 | | (23y/3)-(3y/2)=37 | | 6=24b | | (x-1)(x-1)+3=12 | | -170=10(x-8) | | 4-7+2r+8r= | | -294-110x+4x^2=450 | | w/9.6=3 | | 57=8p+9 | | 33=15x | | 0=4(x+3) | | 3x^2+6xy-9xy= | | (11x+3)2=16 | | -1+2b=-7 | | X-3/4x-5=1 | | 5a/11a | | 3(9+x)=45 | | 9x+3y-5=6x-9y+10 |

Equations solver categories